Thin PEGylated Carbon Nitrides: Water‐Dispersible Organic Nanodots as Bioimaging Probes. Issue 14 (12th February 2018) - Kim, Jin Kwan; Park, Sunghee; Yoo, Ran Ji; Jeong, Hyeon Jin; Oh, Junghoon; Lee, Yong Jin; Park, Sungjin; Kim, Dong Wook
Abstract: Fluorescent materials are being used for the optical/fluorescence imaging of living cells and animal models. As such, the development of heavy‐metal‐free, water‐dispersible, and biocompatible imaging probes is still important. Carbon nitride (C3 N4 ) is used as a bioimaging probe due to its suitable optical properties, thus enhancing its biocompatibility and dispersibility in aqueous media is required. In this study, we incorporated short‐chain polyethylene glycol (PEG) groups onto a carbon nitride network by the simple N‐alkylation of hexaethylene glycolic mesylate with nucleophilic nitrogen atoms on oxidized carbon nitride (OCN). The PEGylated OCN (PEG‐OCN) was well dispersed in water as nanodots with a lateral dimension of approximately 30 nm and a thickness of 0.5–1.2 nm and showed strong photoluminescence in the visible region. Cell‐viability testing confirmed that these "heavy‐metal‐free" organic nanodots were highly biocompatible and noncytotoxic. In particular, the developed nanodots could provide clear confocal images of RAW 264.7 cells without weakening cell activity and displaying any aggregation in a range of concentrations (25–100 μg mL −1 ) with bright‐green emission in the cytoplasm. Abstract : Glowing brightly : Ultrathin polyethylene glycosylated (PEGylated) oxidized carbon nitride (PEG‐OCN) nanodots have been designed and prepared that can act as a physiologically friendly "heavy‐metal free" bioimaging probe. In particular, the developed nanodots provide clear confocal images of RAW 264.7 cells with bright‐green emission in the cytoplasm (see picture; OMs=mesylate).